Customer loyalty in mid-market fashion e-commerce - Orelma, Lilja (My University, 2021)
Mid-market fashion is a growing industry that is primarily focused on offering high-quality apparel with reasonable prices to niche audiences. Simultaneously, fashion e-commerce has seen phenomenal growth during the past decade as more businesses and consumers have moved online. To stay afloat in today’s competitive market, the im-portance of customer loyalty has become more crucial than ever. By understanding how loyalty is formed, businesses can create long-lasting customer relationships and increase their profitability. This study discusses how customer loyalty is formed in the industry of mid-market fashion e-commerce. The purpose of this study is to understand the above by investigat-ing different e-loyalty drivers and explore how consumers’ values reflect on their loyal-ty. The theoretical background of the study consists of literature related to customer loyalty, especially in an online context. This study adopts qualitative research methods, and the empirical research is based on seven consumer interviews. The interview data was collected in the spring of 2020, and all representatives were young professionals living in London, who frequently shop for mid-market fashion online. This study finds that e-loyalty in the context of mid-market fashion is primarily driven by hedonic values, which is the basis for the entire purchasing process. E-loyalty has been found to be a product of trust, perceived value, and satisfaction, which are driven by multiple factors. Ultimately, satisfaction, which is the key to repeat purchas-ing and hence e-loyalty, can be achieved by fulfilling the customers’ expectations. Loyalty in mid-market fashion e-commerce has so far been an unresearched topic. This research provides an overarching framework on how e-loyalty is formed in mid-market fashion e-commerce. In addition to the theoretical contribution, the results of this study are valuable for online retailers who operate in the mid-market fashion sector.

Keskitason muoti on kasvava muodin ala, joka tarjoaa laadukkaita tuotteita kohtuulliseen hintaan, keskittyen rajattuihin asiakasryhmiin. Samanaikaisesti nettikauppa on kasvattanut suosiotaan räjähdysmäisesti viimeisen vuosikymmenen aikana. Jotta yritykset selviäisivät nykypäivän kovasta kilpailusta, uskolliset asiakaat ovat tärkeämpiä kuin koskaan. Ymmärtämällä kuinka asiasuskollisuus muodostuu, yritykset voivat luoda pitkäaikaisia asiakassuhteita ja kasvattaa kannattavuuttaan. Tämä tutkimus tutkii asiakasuskollisuuden muodostumista keskitason muodin nettikaupan alalla. Tutkimuksen tarkoituksena on ymmärtää mikä johtaa asiakasuskollisuuteen. Niinpä tutkimus tutkii seikkoja, jotka johtavat uskollisuuteen. Samalla tutkimus pyrkii ymmärtämään, miten asiakkaiden arvot vaikuttavat uskollisuuteen. Tutkimuksen tavoitteen saavuttamiseksi tutkittiin olemassaolevaa akateemista kirjallisuutta asiakasuskollisuuteen liittyen, eriyisesti nettiuskollisuuteen keskittyen. Tämän lisäksi tutkimus käytti kvalitatiivisia tutkimusmenetelmiä, ja empiirinen tutkimus perustuu seitsemään kuluttajahaastatteluun. Haastatteluaineisto kerättiin keväällä 2020, ja kaikki haastateltavat olivat nuoria ammattilaisia, jotka asuvat Lontoossa ja ostavat keksitason muotia netistä toistuvasti. Tämä tutkimus osoittaa, että nettiuskollisuus keskitason muodin parissa pohjautuu pääasiassa hedoistisiin arvoihin, jotka ovat edellytys koko ostoprosessille. Nettiuskollisuuden todettiin olevan luottamuksen, oletetun arvon sekä tyytyväisyyden tuotos, jotka puolestaan johtuvat useista eri tekijöistä. Tyytyväisyys, joka on tärkein ehto nettiuskollisuudelle, pohjautuu ennen kaikkea asiakkaiden odotusten täyttämiseen. Nettiuskollisuus keskitason muodin parissa oli toistaiseksi tutkimaton aihe. Tämä tutkimus laati teoreettisen viitekehyksen sille, miten nettiuskollisuus kehittyy keskitason muodin parissa. Teoreettisen kontribuution lisäksi tutkimuksen tulokset ovat hyödyllisiä keskitason muodin vähittäismyyjille.
Keywords: Customer loyalty, e-commerce, mid-market fashion